2017
DOI: 10.1163/22134808-00002570
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration in Migraine: Recent Developments

Abstract: There are well-documented unimodal sensory differences in migraine compared to control groups both during, and between migraine attacks. There is also some evidence of multisensory integration differences in migraine groups compared to control groups, however the literature on this topic is more limited. There are interesting avenues in the area of visual–vestibular integration, which might have practical implications, e.g., motion sickness and nausea in migraine. Recent work has been investigating the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Migraine is a common neurological disorder characterised by a unilateral, pulsating headache with moderate to severe pain. Migraines are accompanied by changes in sensory processing, including heightened sensitivity to light (photophobia) and sound (phonophobia), and altered multisensory processing (for reviews see, O'Hare, 2017, andSchwedt, 2013).…”
Section: Migraine and Headachesmentioning
confidence: 99%
“…Migraine is a common neurological disorder characterised by a unilateral, pulsating headache with moderate to severe pain. Migraines are accompanied by changes in sensory processing, including heightened sensitivity to light (photophobia) and sound (phonophobia), and altered multisensory processing (for reviews see, O'Hare, 2017, andSchwedt, 2013).…”
Section: Migraine and Headachesmentioning
confidence: 99%
“…This is indeed a surprising and unexpected result. It is generally accepted in the literature that altered multisensory processing is a characteristic feature of migraine (25)(26)(27)(28)(29), but, to our knowledge, no study before has reported enhanced multisensory performance in migraine patients. Furthermore, improved associative learning performance was accompanied by significantly shorter reaction times, which is exactly what one expects in the context of multisensory facilitation (30).…”
Section: Discussionmentioning
confidence: 85%
“…However, studies on cyclic changes of multisensory integration across different phases are still lacking. The investigation into the mechanisms of how multisensory integration changes across migraine phases may provide new insight into the generation of migraine attacks [10,54].…”
Section: Multisensory Integrationmentioning
confidence: 99%